Cerita Anak sebagai Media Pembentuk Karakter Anak - Ferdian Achsani (Magister Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mulawarman, 2018)
Literature and character education are two things that can not be separated. Literature as a reflection of the life of the community, generally teaches the reader to be able to understand the wisdom of the displayed story. Literature can be used as a medium of learning, especially in the process of internalization of the value of character education to learners. The value of character education in the literary work is expected to be followed by the students. Currently Indonesia is experiencing moral degradation. The need for moral cultivation to the learners aims to create human beings who are virtuous in the future. Each subject has the right to internalize character education to learners. So in the Indonesian language, the process of characterization of character education can be done when learning on literary materials. This study aims to describe the value of character education in Solopos children's stories. this research is included in qualitative discrptive research. The results of this study concluded that in the story Solopos child, there is a value of character education that can be taught to learners, especially at elementary school level. The results showed that this child's story can be used as a reference for teachers, as a medium to internalize character education at elementary school level.